Reinventing talent management : principles and practices for the new world of work - Lawler, Edward E., III (Berrett-Koehler Publishers, Inc., 2017)
This book teaches managers and human resource executives how to identify a comprehensive and integrated set of talent practices that fit the evolving workplace, and that will dramatically improve the effectiveness of all organizations.